Longitudinal studies of ageing: Implications for future studies - Peut, A; Logie, H; Hogan, R (My University, 2004)
This report examines a selection of recent, current and planned Australian longitudinal studies relevant to ageing in respect of their methodological features and data collection scope. The report also compares features of these studies with some well established overseas longitudinal projects. It is intended that the report be a practical resource for researchers, research funders and policy makers, supporting future efforts to address ageing research needs in Australia. Appendices provide a comparative matrix of the 23 studies examined, and details of the studies under the headings: study aims; contact details; location of research; investigators; content; funding agencies/ budget; data availability; response rate; methods and data collection; data analysis; results; outputs; and related studies. The studies reviewed were: English Longitudinal Study of Ageing; Baltimore Longitudinal Study of Aging; Australian Longitudinal Study of Ageing; 45 and Up; The Dubbo Study of the Health of the Elderly; Melbourne Longitudinal Studies on Healthy Ageing Program; The Sydney Older Persons Study; Healthy Retirement Project; Stories of Ageing; Canberra Longitudinal Study of Ageing; Florey Adelaide Male Ageing Study; Melbourne Collaborative Cohort Study (Health 2000); A Longitudinal Study of Bone Loss in Men; The South Australian Dental Longitudinal Study; Australian Longitudinal Study of Women's Health; PATH Through Life Project; Negotiating the Life Course; The Household Income and Labour Dynamics in Australia Survey; Longitudinal Study of Immigrants to Australia; AusDiab Follow-up Study; Australian Temperament Project; Growing Up in Australia; Longitudinal Surveys of Australian Youth.
Keywords: Health; Health -- Wellbeing; Health and wellbeing; Health; Wellbeing; Health and wellbeing